Urbanization and Social Cohesion : Challenges and Opportunities in Rapidly Growing Cities - Wei Ming Tan; Lian Chen (International Journal of Humanities and Social Sciences Reviews, 2024)
This study investigates how rapid urbanization affects social cohesion in growing cities, with a focus on the dynamics of community building, social integration, and inequality. Through case studies of megacities, the research examines challenges such as housing shortages, resource distribution, and community displacement. Findings suggest that while urbanization offers economic opportunities, it requires effective policies to maintain social bonds and prevent fragmentation.